2023
DOI: 10.3390/f14030572
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Challenges for Forest Commons (Iriai Forest) Management in Japan: A Focus on Forest Producers’ Cooperatives and Authorized Neighborhood Associations

Abstract: Iriai forests are an example of communal forest management in Japan. Local institutions have never been static in governing iriai forests and the external environments of iriai forests have changed significantly over time. This study examines the management challenges of forest producers’ cooperatives (FPCs) and authorized neighborhood associations (ANAs) as the two most important contemporary forms of iriai forest management. Data from nine FPCs and three ANAs in the Fukuoka and Saga prefectures of Kyushu Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A previous study [17] revealed that as the generation involved in afforestation ages and retires, management succession fails, forest management and boundaries become unclear, and the level of forest management declines, particularly in micro-owned areas. Even in many forest producers' cooperatives and authorized neighborhood associations that were established by reorganizing the remaining historical forest commons (Iriai Forest), management is becoming increasingly difficult owing to low timber prices, a decreased number of members, and tax burdens [18]. Ota also emphasized that the members had maintained an attachment to and responsibility for the forests of Iriai origin and a sense of public contribution.…”
Section: Literature Review On Current Forestry Issues In China and Japanmentioning
confidence: 99%
“…A previous study [17] revealed that as the generation involved in afforestation ages and retires, management succession fails, forest management and boundaries become unclear, and the level of forest management declines, particularly in micro-owned areas. Even in many forest producers' cooperatives and authorized neighborhood associations that were established by reorganizing the remaining historical forest commons (Iriai Forest), management is becoming increasingly difficult owing to low timber prices, a decreased number of members, and tax burdens [18]. Ota also emphasized that the members had maintained an attachment to and responsibility for the forests of Iriai origin and a sense of public contribution.…”
Section: Literature Review On Current Forestry Issues In China and Japanmentioning
confidence: 99%